Flame Retardant Composite from Oil Palm Trunk - Madihan, Yusof; Junidah, Lamaming; Rokiah, Hashim (UTS Publisher, 2025)
The use of oil palm biomass waste as a potential substitute for wood in buildings is consistent with the new idea of green economy development for a sustainable economic system. Nonetheless, investigating and determining the optimal production technique continues to be difficult for researchers. After the age of 25, oil palm trunks are typically chopped down because of dwindling productivity or because they have gotten too tall, making harvesting extremely challenging (Lamaming et al., 2017). According to Awalludin et al. (2015), oil palm trunks may typically be processed mechanically to create products with additional value. Because of economic factors, these raw materials are typically readily available and reasonably priced..